Mutations within the selectivity filter of the NMDA receptor-channel influence voltage dependent block by 5-hydroxytryptamine - Kloda, A (Nature Publishing Group, 2006)
BACKGROUND AND PURPOSE: Voltage-dependent block by Mg(2+) is a cardinal feature of NMDA receptors which acts as a coincidence detector to prevent the receptor from over-activation. Inhibition of NMDA receptor currents by 5-hydroxytryptamine (5-HT) indicated that 5-HT, similar to Mg(2+), binds within the membrane electric field. In the present study, we assessed whether point mutations of critical asparagine residues located within the selectivity filter of NR1 and NR2A subunits of NMDA receptor-channel affect voltage-dependent block by 5-HT. EXPERIMENTAL APPROACH: The mode of action of 5-HT and Mg(2+) on wild-type and mutated NMDA receptor-channels expressed in Xenopus oocytes was investigated using the two-electrode voltage clamp recording technique. KEY RESULTS: The mutation within the NR1 subunit NR1(N0S or N0Q) strongly reduced the voltage dependent block by 5-HT and increased the IC(50). The corresponding mutations within the NR2 subunits NR2A(N0Q or N+1Q) reduced the block by 5-HT to a lesser extent. This is in contrast to the block produced by external Mg(2+) where a substitution at the NR2A(N0) and NR2A(N+1) sites but not at the NR1(N0) site significantly reduced Mg(2+) block. CONCLUSION AND IMPLICATIONS: The block of NMDA receptor-channels by 5-HT depends on the NR1-subunit asparagine residue and to a lesser extent on the NR2A-subunit asparagine residues. These data suggest that the interaction of 5-HT with functionally important residues in a narrow constriction of the pore of the NMDA receptor-channel provides a significant barrier to ionic fluxes through the open channel due to energetic factors governed by chemical properties of the binding site and the electric field.